A case report of Andersen-Tawil syndrome misdiagnosed with myodystrophy - Zhao, Xiuqin; Zu, Hengbing; Yao, Kai (Frontiers in Neurology, 2023)
Andersen Tawil syndrome (ATS) is a rare periodic paralysis caused by the KCNJ2 gene mutation. Here we report an ATS patient misdiagnosed with myodystrophy. A 66-year-old man presented with a 60 years history of episodic weakness in the proximal muscle of upper and lower limbs. The man has been diagnosed with muscle pathology and experienced genetic examinations in many hospitals since childhood. We conducted a correct diagnosis in combination with the patient history, electrical physiology, and genetic analysis identified a heterozygous KCNJ2 gene variant (c.220A>G; p.T74A). Patients with ATS can develop permanent myasthenia characterized by chronic progressive myopathy. ATS patients should also pay special attention to the risks of anesthesia in surgery, including malignant hyperthermia (MH), muscle spasms affecting tracheal intubation or ventilation, and ventilator weakness. Early diagnosis and therapy could help delay the onset of myasthenia and avoid the risks of anesthesia accidents.